Ifo World Economic Survey June 2003 - Gernot Nerb; Anna Stangl (Ifo World Economic Survey, 2003)
World Economic Climate: The current economic situation of the world economy still less satisfactory - Economic Expectations: Economic expectations for the next six months slightly deteriorated, but remained positive - Inflation: Inflation under control in most countries - Interest Rates: Only small scope seen for further rate cuts - Currencies: Euro is seen as somewhat overvalued - Special Topic: WES experts see some problems in new trade rules to forestall terrorist threats
Keywords: 330